Protein Sorting in Plasmodium Falciparum - D.C. Ghislaine Mayer (Life, 2021)
Plasmodium falciparum is a unicellular eukaryote with a very polarized secretory system composed of micronemes rhoptries and dense granules that are required for host cell invasion. P. falciparum, like its relative T. gondii, uses the endolysosomal system to produce the secretory organelles and to ingest host cell proteins. The parasite also has an apicoplast, a secondary endosymbiotic organelle, which depends on vesicular trafficking for appropriate incorporation of nuclear-encoded proteins into the apicoplast. Recently, the central molecules responsible for sorting and trafficking in P. falciparum and T. gondii have been characterized. From these studies, it is now evident that P. falciparum has repurposed the molecules of the endosomal system to the secretory pathway. Additionally, the sorting and vesicular trafficking mechanism seem to be conserved among apicomplexans. This review described the most recent findings on the molecular mechanisms of protein sorting and vesicular trafficking in P. falciparum and revealed that P. falciparum has an amazing secretory machinery that has been cleverly modified to its intracellular lifestyle.